Moving PhD and DNP Collaboration Forward in Clinical Settings: A Literature Review - Susan B. Fowler; Charlene Pope; Julius Kehinde (Journal of Doctoral Nursing Practice, 2026)
Background: PhD-prepared nurses generate new evidence, while Doctor of Nursing Practice (DNP)-prepared nurses translate evidence into practice. While doctoral-prepared nurses have different foci, they can use their skills together to advance the art and science of nursing. Objective: The purpose of this project was to review the recent literature on PhD and DNP collaboration and suggest recommendations for partnerships in clinical settings. Methods: A literature search was conducted using two databases and keywords, which resulted in 20 pertinent articles reviewed for focus and findings. Results: Literature supports PhD and DNP collaboration with clear benefits in positive clinical outcomes, enhanced use of theory and methods, teamwork, increased project completion, and shared learning. Despite these benefits, barriers continue with role ambiguity, limited opportunities for collaboration, and hierarchical philosophies. Conclusion: There is strong support for PhD and DNP collaboration but challenges impact operationalizing it in practice. Implications for Nursing: Collaboration between PhD- and DNP-prepared nurses presents a compelling model for advancing clinical practice, research translation, and professional development but requires targeted efforts to support and enhance professional opportunities.